Αισθητήρες με σύνθετα υλικά γραφένιου/πολυμερούς - Λιακόπουλος, Βασίλειος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2015)
The aim of this thesis was the preparation and the study of nanocomposite materials consisting of polymer matrix and carbon nanotubes as filler, for the characterization of their gas sensing properties. Graphene nanoplatelets (GnP) were selected as filler nanoparticle due to their excellent electrical, mechanical and thermal properties. The mechanism according to which the detection of gases was studied, concerns the change in electrical resistance of nanocomposites exposed to analyte gas, due to the partial destruction of the conducting network formed by GnPs throughout the insulating matrix. The preparation of nanocomposite polymer materials, with dispersion of conductive fillers within the matrix, was achieved by the solution mixing and the sonication techniques. In order to form thin films, the fabricated (GNP)/ Poly(methylmethacrylate) (PMMA) and (GNP)/ Epoxy (EPR) nanocomposites were deposited on gold interdigitated electrodes using the drop casting method. A two step lift-off method, for the fabrication of a graphene nanoplatelets (GNP)/ Poly(methylmethacrylate) (PMMA) and (GNP)/ Epoxy (EPR) nanocomposite chemical sensor is presented. Polyvinyl alcohol (PVA) is used as sacrificial layer to precisely pattern the chemically selective layer. The main advantage of PVA is its solubility to water which simplifies the whole process. The study and characterization of sensing properties of nanocomposite films, took place using an appropriate device provided by institute of microelectronics NCSR Demokritos . This device allows firstly the preparation of gas mixtures with regulated concentration and secondly the electrical measuring of nanocomposites exposed to analyte gases. The sensor is evaluated using water with concentrations of 500ppm to 20000ppm.